Occurrence of Symphyla (Myriapoda) in the region of the Upper Solimões River, Amazonas, Brazil - Morais, José Wellington de; Silva, Ester Paixão da (Pesquisa Agropecuaria Brasileira, 2010)
The present work aimed at identifying the Symphyla species diversity and abundance in various land-use systems under different degrees of intensification in western Amazonia. This is the first inventory of Symphyla in primary and secondary forest, crops, agroforestry systems and pastures which was carried out in Benjamin Constant municipality, in the region of the Upper Solimões River, Brazil. Samples (n = 101) were collected using a metal corer, and the symphylan extraction was carried out using Berlese-Tullgren funnels. Two genera and three species of symphylans were encountered. Considering the diversity encountered in Amazonian inventories, with only four genera and five known species overall, the three species found in the present study are considered a reasonable representation of the regional diversity. Two of the Hanseniella species found have been known to cause plant damage.